A new species of the genus Pagurus Fabricius, 1775 (Crustacea: Decapoda: Anomura: Paguridae) from the Ryukyu Islands, southwestern Japan - Osawa, Masayuki (Zootaxa, 2012)
A new species of pagurid hermit crab, Pagurus tabataorum n. sp., is described from Kume Island, Ryukyu Islands,southwestern Japan. It appears closest to P. capsularis McLaughlin, 1997, known from the Tanimbar Islands in Indonesia,but is readily distinguished by the possession of numerous arcuate or sinuous, transverse scutes on the dorsal surface ofthe chelae. Distributional patterns of species of the genus Pagurus Fabricius, 1775, hitherto recorded from the Ryukyu Islands are briefly reviewed.